PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DOK KAPAL PT. PARTSINDO ABADI SAMARINDA - AIDIL FITRA, APRILLA ANUGRAH (EKONOMIA, 2015)
Purpose of this study was to determine the effect of service quality in the form of ( responsiveness, assurance, emphaty, reliability, and tangibles) significantly influence consumer satisfaction in PT. Partsindo Abadi Samarinda. Whether factors such as quality of service (responsiveness, assurance, emphaty, reliability, and tangibles ) all affect the satisfaction of the PT. Partsindo Abadi Samarinda.Marketing management is to set the level, timing and nature of the request in a way that can help the organization achieve its goals as expected. The first hypothesis in this study is the quality of service that consists of variable responsiveness, assurance, emphaty, reliability, and tangibles significant effect on customer satisfaction at PT. Partsindo Abadi Samarinda. The second hypothesis variable responsiveness significant effect on customer satisfaction.Data collection techniques drawn from the population and the number of samples, for the study population are consumers PT. Partsindo Abadi Samarinda while samples taken from a small portion of the population is considered to represent the overall respondents. In this study, the researchers took a sample of 30 respondents. Sampling technique using purposive random sampling means sampling technique was based on consumers who come to order the ship or ship repair.Data that had been collected were analyzed using multiple linier regression. The formula used to calculate multiple linier regression is : Y = a + b1X1 + b2X2 + b3X3 + b4X4 + b5X5 + e. Author using SPSS.Hypothesis testing is done in two ways by using the F test and T test. The first hypothesis testing using the F test is used to determine the regression coefficients simultan independent variables have an influence on the dependent variable or not. While the second hypothesis testing is done with T test, to test separately the effect of independent variables on the dependent variable.Of the results obtained in this study concluded that the simultan analysis, the variable quality of service that is responsiveness, assurance, empathy, reliability and tangibles effect on customer satisfaction and this supports the first hypothesis. The second hypothesis is the variable responsiveness significantly influence consumer satisfaction PT. Partsindo Abadi Samarinda.